The first examples of multiply bonded dirhenium(iii, ii) paramagnetic complexes containing nitrobenzoate ligands: spectroscopic, structural, cytotoxicity and computational studies. Issue 17 (9th February 2017) - Mallick, Suman; Ghosh, Mrinal Kanti; Mandal, Suman; Rane, Vinayak; Kadam, Ramakant; Chatterjee, Annesha; Bhattacharyya, Arindam; Chattopadhyay, Swarup
Abstract : The synthesis and structural characterization of the hitherto unreported multiply bonded paramagnetic dirhenium(iii, ii ) nitrobenzoate complexes have been reported. Abstract : 4-Nitrobenzoic acid, 3-nitrobenzoic acid and 4′-nitro[1, 1′-biphenyl]-4-carboxylic acid react with the multiply bonded paramagnetic dirhenium(iii, ii ) complex Re2 (μ-O2 CCH3 )Cl4 (μ-Ph2 PCH2 PPh2 )2 (1 ) in refluxing ethanol to afford the paramagnetic substitution products of the type Re2 (μ-L)Cl4 (μ-Ph2 PCH2 PPh2 )2, where L represents the nitrobenzoate ligands [L = 4-nitrobenzoate, 2 ; 3-nitrobenzoate, 3 ; 4′-nitro[1, 1′-biphenyl]-4-carboxylate, 4 ]. These are the first examples of paramagnetic dirhenium complexes containing nitrobenzoate ligands. The spectral (UV-vis, IR, and EPR) and electrochemical properties of the complexes are described. The identity of4 has been established by single-crystal X-ray structure determination (Re–Re distance of 2.2967(4) Å). The electronic structures of the complexes were scrutinized by density functional theory (DFT) calculations. X-band EPR spectral measurements along with the DFT analysis show that the unpaired electron resides in the metal–metal δ* antibonding orbital. The complexes were also screened in vitro for their antiproliferative properties against the human breast cancer cell line MCF-7 by the MTT assay. Flow cytometry analysis showed that the complexes arrested the sub-G0/G1 phase.